2017
DOI: 10.7326/m16-1700
|View full text |Cite
|
Sign up to set email alerts
|

Intradiscal Glucocorticoid Injection for Patients With Chronic Low Back Pain Associated With Active Discopathy

Abstract: French Ministry of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 34 publications
1
58
0
5
Order By: Relevance
“…Bisphosphonates do not only inhibit osteoclasts; they have also shown to suppress the secretion of proinflammatory cytokines such as IL-1, TNF-A, and IL-6 [31]. Several studies have found upregulation of pro-inflammatory cytokines in endplates with MC [32][33][34] and local anti-inflammatory treatment with glucocorticoid has shown to have a short-term alleviating effect on LBP [35]. In our RCT, the improvement in LBP in the ZA group [21] could have been due to the general ability of bisphosphonates to regulate bone turnover by suppressing osteoclast activity [36] or to direct anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates do not only inhibit osteoclasts; they have also shown to suppress the secretion of proinflammatory cytokines such as IL-1, TNF-A, and IL-6 [31]. Several studies have found upregulation of pro-inflammatory cytokines in endplates with MC [32][33][34] and local anti-inflammatory treatment with glucocorticoid has shown to have a short-term alleviating effect on LBP [35]. In our RCT, the improvement in LBP in the ZA group [21] could have been due to the general ability of bisphosphonates to regulate bone turnover by suppressing osteoclast activity [36] or to direct anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…. get over it," a statement some in the privacy industry took as tantamount to a declaration of war [54]. In 2009, when asked whether users considered Google a 'trusted friend,' former Google CEO Eric Schmidt responded, "If you have something that you don't want anyone to know, maybe you shouldn't be doing it in the first place."…”
Section: A Typology Of Privacy Culturesmentioning
confidence: 99%
“…Ähnliche Ergebnisse zeigte eine aktuelle PRCT mit 135 Patienten mit einer Modic-I-Osteochondrose (auch als aktive, mit einem Ödem der angrenzenden Grund-und Deckplatten einhergehend bezeichnete Osteochondrose), die diskografisch positiv waren; sie bekamen entweder Prednisolon oder keine weitere Injektion nach Diskografie. Auch hier war der positive Effekt nur 4 Wochen nach Injektion signifikant nachweisbar, während nach 1 Jahr kein signifikanter Unterschied zwischen den Gruppen bestand [44]. Zusammenfassend gibt es derzeit keine sichere Evidenz für einen langfristigen Effekt einer intradiskalen Steroidinjektion beim diskogenen Schmerz.…”
Section: Intradiskale Injektionen Beim Diskogenen Schmerz/ Osteochondunclassified